Enhanced 5-Aminolevulinic Acid Production by Co-expression of Codon-Optimized hemA Gene with Chaperone in Genetic Engineered Escherichia coli - Yu, Tzu-Hsuan; Yi, Ying-Chen; Shih, I-Tai; Ng, I-Son (Applied biochemistry and biotechnology, 2020)
5-Aminolevulinic acid (ALA) is an important metabolic intermediate compound with high value and has recently been used in agriculture and medicine. In this study, we have constructed six recombinant Escherichia coli ( E. coli ) strains that are involved in pET system under the regulation of the T7 promoter and LacI to express codon-optimized hem A gene from Rhodobacter capsulatus (RchemA) for ALA production via the C4 pathway. Due to codon optimization, hem A has a high transcriptional level; however, most RcHem A proteins were formed as inclusion body. To improve expression in soluble form, the vector with TrxA fusion tag was successfully used and co-expressed with partner GroELS as chaperone in another vector. As a result, ALA production increased significantly from 1.21 to 3.67 g/L. In addition, optimal ALA production was developed through adjustment of induction time and isopropyl β-D-1-thiogalactopyranoside (IPTG) concentration, as well as substrate addition conditions. By adopting a two-stage induction strategy, the highest ALA reached 5.66 g/L when 0.1 mM of IPTG was added at early exponential phase (i.e., OD 600 was equal to 0.7 to 0.8), while 6 g/L of glycine, 2 g/L of succinate, and 0.03 mM of pyridoxal 5′-phosphate (PLP) were provided in the mid-exponential phase in fermentation.